The Effectiveness of Cooperative Role Play Activities in Improving Junior High School Students Speaking Confidence - Finy Widya Fransiska (Universitas Muhammadiyah Lampung, 2025)
Speaking confidence is a crucial affective factor that influences students willingness and ability to communicate in English. However, many junior high school students experience low speaking confidence due to anxiety, fear of making mistakes, and limited opportunities for meaningful oral practice. This study aimed to examine the effectiveness of cooperative role play activities in enhancing students speaking confidence in English learning. A quantitative approach was employed using a quasi-experimental one-group pretestposttest design. The participants consisted of 32 eighth-grade students selected through total sampling. Data were collected through a speaking confidence questionnaire, a speaking performance test, and classroom observation. The speaking confidence questionnaire and speaking test were administered before and after the implementation of cooperative role play activities. The treatment was conducted over six instructional meetings, during which students participated in structured role play scenarios in small groups. The data were analyzed using descriptive statistical analysis by comparing the mean scores of pretest and posttest results. The findings revealed a significant improvement in students speaking confidence after the implementation of cooperative role play activities. The mean score of speaking confidence increased from 61.25 in the pretest to 78.40 in the posttest, showing a gain of 17.15 points. Similarly, students speaking performance improved from a mean score of 64.10 to 80.35, with a gain of 16.25 points. Classroom observation results supported these findings, indicating increased student participation, reduced hesitation, and more active peer interaction during speaking activities. Based on these results, it can be concluded that cooperative role play activities are effective in improving students speaking confidence and speaking performance in English learning. The study suggests that role play can be an effective instructional strategy for fostering communicative competence and confidence among EFL learners.